Correlation Between Research Productivity During Medical School and Radiation Oncology Residency - Daniel Huang, MD; Muhammad M. Qureshi, MBBS, MPH; Minh T. Truong, MD; Ariel E. Hirsch, MD (Advances in Radiation Oncology, 2023)
Purpose: This analysis investigates whether research productivity during medical school predicts future research productivity during radiation oncology residency. Methods and Materials: At our institution, there have been 20 medical students who graduated between 2005 and 2015 and subsequently completed their residency training in radiation oncology. We built a database of all PubMed-indexed publications in which these former students were the first author or coauthor. Mean publication rates with 95% confidence intervals (95% CI) were computed. The paired t test and McNemar-Bowker test of symmetry were used to examine differences in first-author and coauthor publications between the medical school and residency periods. An ordinal logistic regression model was employed to measure the odds ratio of publishing during residency versus during medical school. A Spearman correlation coefficient was calculated for the relationship between the number of publications during medical school and the number during residency. Results: A total of 14 and 60 first-author publications (46 and 117 coauthor publications) were identified for 20 individuals during medical school and residency, respectively. There was an average of 0.7 (95% CI, 0.17-1.23) first-author publications during medical school and 3.08 (95% CI, 1.56-4.44) first-author publications during residency (P = .003). Only 15% (3/20) had ≥2 publications during medical school, and 50% (10/20) had ≥2 publications during residency (P = .012). The Spearman correlation coefficient between research publications before and during residency was .457 (P = .043). The mean number of coauthor publications during medical school and residency was 2.3 (95% CI, 0.92-3.68) and 5.85 (95% CI, 3.50-8.20), respectively (P = .004). Conclusions: Based on this retrospective analysis from our institution, student research productivity during medical school, as defined by the number of first-author publications, does correlate with future research productivity during radiation oncology residency.